Status and trends in the structure of Arctic benthic food webs - Kędra, Monika; Moritz, Charlotte; Choy, Emily S.; David, Carmen; Degen, Renate; Duerksen, Steven; Ellingsen, Ingrid; Górska, Barbara; Grebmeier, Jacqueline M.; Kirievskaya, Dubrava; van Oevelen, Dick; Piwosz, Kasia; et al. (Polar research, 2015)
Ongoing climate warming is causing a dramatic loss of sea ice in the Arctic Ocean, and it is projected that the Arctic Ocean will become seasonally ice-free by 2040. Many studies of local Arctic food webs now exist, and with this review paper we aim to synthesize these into a large-scale assessment of the current status of knowledge on the structure of various Arctic marine food webs and their response to climate change, and to sea-ice retreat in particular. Key drivers of ecosystem change and potential consequences for ecosystem functioning and Arctic marine food webs are identified along the sea-ice gradient, with special emphasis on the following regions: seasonally ice-free Barents and Chukchi seas, loose ice pack zone of the Polar Front and Marginal Ice Zone, and permanently sea-ice covered High Arctic. Finally, we identify knowledge gaps in different Arctic marine food webs and provide recommendations for future studies.